Estimating the memory parameter for potentially non-linear and non-Gaussian time series with wavelets. (31st January 2022) - Xu, Chen; Zhang, Ye
Abstract: The asymptotic theory for the memory-parameter estimator constructed from the log-regression with wavelets is incomplete for 1/ f processes that are not necessarily Gaussian or linear. Having a complete version of this theory is necessary because of the importance of non-Gaussian and non-linear long-memory models in describing financial time series. To bridge this gap, we prove that, under some mild assumptions, a newly designed memory estimator, named LRMW in this paper, is asymptotically consistent. The performances of LRMW in three simulated long-memory processes indicate the efficiency of this new estimator.